The development of multicultural education comics to embed tolerance character for 4th grade of elementary school - Albi Anggito; E. Kus Eddy Sartono (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This research aims to produce a comic book that can be used to embed the character of tolerance to the students of 4th grade of elementary school. This research using development procedure from Borg and Gall includes seven steps procedure, they are research and information collecting, planning, developing a preliminary form of product, preliminary field testing, main product revision, main field testing, and operational product revision. The data resources were collected from interviews, observation, and questionnaires. Data analysis technique by quantitative descriptive statistics. Preliminary field tests involve three students and one class teacher. Main field tests involve twelve students and one class teacher. Final validation by material expert got an average score of 4.53, language expert got an average score of 4.50, and media expert got an average score of 4.25. The preliminary field-testing result got an average score of 4.50 in teachers and got an average score of 3.46 in students. The main field-testing result got an average score of 4.75 in teachers and got an average score of 4.74 in students. So, education comics can be used properly to embed tolerance characters in elementary school.